TEACHERS’ TECHNIQUES AND PROBLEMS IN TEACHING READING - Yanuarti Apsari; Yana Yana (IKIP Siliwangi Bandung, 2015)
ABSTRACT This study is aimed at exploring teachers’ techniques in teaching reading comprehension at one senior high school in Bandung Barat and investigating exploring the problems that the teachers encountered in teaching reading. This study employed a case study research design which used two data collection, observation and questionnaire. Two English teachers were purposively selected to participate in this research. Then, they were analyzed and reported descriptively. After being analyzed, the data revealed that the respondents used the teaching reading comprehension techniques in three reading stages: pre-reading, while-reading, and post-reading stages. In pre-reading stage, they applied Previewing technique and Vocabulary Instruction Technique; Pre-Reading Questions and Brainstorming Technique and discussing text type. Then, in while reading stage, they used Question-Answering Techniques, Vocabulary Instruction Technique, Recitation and Reading aloud. In post-reading stage, they conducted reviewing technique and follow up strategy. The data also indicated that in teaching reading comprehension, there were four problems encountered by the respondents in teaching reading: lack of students’ vocabulary mastery, lack of motivation in reading, students were not used to read a lot on a regular basis and teaching time allocation. With reference to the findings, it is recommended for English teacher to select appropriate technique in teaching reading which is relevant to the students’ needs. In addition, the teachers also are expected to improve their ability in teaching practice. It can be done through joining some trainings and workshops about techniques in teaching, reading a lot of sources, and sharing information with others teachers. Key Words: Teacher’s Techniques, Reading Comprehension and Problem. ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi teknik guru dalam membaca pemahaman mengajar di salah satu SMA di Bandung Barat dan menyelidiki menjelajahi masalah yang dihadapi guru dalam membaca mengajar. Penelitian ini menggunakan desain penelitian studi kasus yang menggunakan dua pengumpulan data, observasi dan kuesioner. Dua guru bahasa Inggris secara sengaja dipilih untuk berpartisipasi dalam penelitian ini. Kemudian, mereka dianalisis dan dilaporkan secara deskriptif. Setelah dianalisis, data menunjukkan bahwa responden menggunakan teknik membaca pemahaman ajaran dalam tiga tahap membaca: pra-membaca, sementara-membaca, dan tahap pasca-membaca. Pada tahap pra-membaca, mereka menerapkan teknik dan Teknik Kosakata Instruksi Meninjau; Pre-Reading Pertanyaan dan Brainstorming Teknik dan mendiskusikan jenis teks. Kemudian, di saat membaca panggung, mereka menggunakan Pertanyaan-Menjawab Teknik, Kosakata Instruksi Teknik, Zikir dan Membaca dengan suara keras. Pada tahap pasca-membaca, mereka yang dilakukan meninjau teknik dan menindaklanjuti strategi. Data ini juga menunjukkan bahwa dalam membaca pemahaman ajaran, ada empat masalah yang dihadapi oleh responden dalam membaca ajaran: kurangnya penguasaan kosakata siswa, kurangnya motivasi dalam membaca, siswa tidak digunakan untuk banyak membaca secara dan pengajaran waktu yang teratur alokasi. Dengan mengacu pada temuan, disarankan untuk guru bahasa Inggris untuk memilih teknik yang tepat dalam membaca mengajar yang relevan dengan kebutuhan siswa. Selain itu, guru juga diharapkan dapat meningkatkan kemampuan mereka dalam praktek mengajar. Hal ini dapat dilakukan melalui beberapa bergabung pelatihan dan lokakarya tentang teknik dalam mengajar, membaca banyak sumber, dan berbagi informasi dengan guru lain. Kata Kunci: Teknik Guru, Pemahaman Membaca dan Masalah.